Controlling factors in the interferometric coherence derived from Sentinel-1 images: an example from the Río Chubut Lower Valley, Argentina. Issue 27 (13th December 2022) - Scivetti, Nicolas; Bilmes, Andrés; Rostagno, Cesar M.; Kaless, Gabriel; Marcos, Paulo; Prieto, María E.; Cuitiño, José I.; Falco, Juan I.; Pascual, Miguel A.; Lucas, Sebastián; Bouza, Pablo J.
Abstract: In this article, controlling factors on radar interferometric coherence (IC) in a region of the Chubut River are analysed, since its variations could indicate potential sediment transfer zones. Studied control factors are vegetation cover, development of the drainage network, rainfall and winds. The results show that the major control over IC loss is given by rainfalls. A secondary control is exerted by the drainage networks development; whereas the limited changes in the vegetation cover and winds regime would not exert significant control. In addition, a permanent IC loss tendency was recognized in channelized areas whereas temporal IC variations were recognized in non-channelized areas. Finally, as different sectors of the study area under the same known conditions (meteorological phenomena, drainage network and vegetation cover) present different IC variations, the existence of at least a third control factor —likely linked to the geology of the landscape—, is deduced from this research.